How exploitative leadership influences employee innovative behavior: the mediating role of relational attachment and moderating role of high-performance work systems. Issue 2 (28th December 2020) - Wang, Zhining; Sun, Chuanwei; Cai, Shaohan
Abstract : Purpose: The purpose of this research is to examine the relationship between exploitative leadership and employee innovative behavior and explore the mediating role of relational attachment and the moderating role of high-performance work systems (HPWSs). Design/methodology/approach: This research collected data from 374 employees and their direct supervisors in 75 teams and tested a cross-level moderated mediation model using multilevel path analysis. Findings: The results suggest that (1) exploitative leadership has a negative impact on employee innovative behavior; (2) relational attachment mediates the relationship between exploitative leadership and employee innovative behavior; (3) HPWS positively moderates the relationship between exploitative leadership and relational attachment and (4) HPWS moderates the mediating mechanism from exploitative leadership to employee innovative behavior. Practical implications: The empirical findings suggest that organizations should make efforts to prevent exploitative leadership. Moreover, managers should pay attention to the important role of relational attachment in promoting employee innovative behavior and realize the role of HPWSs in facilitating the negative effects of exploitative leadership. Originality/value: This research identifies relational attachment as a key mediator that links exploitative leadership to innovative behavior and reveals the role of HPWSs in strengthening the negative effects of exploitative leadership on employee innovative behavior.